Diksi Cermin Realita Budaya dalam Lirik Lagu Populer Indonesia - M Hermintoyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Creative authors will be sensitive to their environment and their development according to their times. Through the diction that is used shows the ability of the author in writing song lyrics. Understanding the song lyrics is not only understanding the language code, but requires the literary code and cultural code. Lyrics in the language code seen in their basic form are meaningful series of words. The words used in showing its beauty are manifested as poetry or lyrics whose meanings are figurative. These figurative words can be seen in the intrinsic elements of majas-literary works and so on. These words are used by the author as a means of creativity through the existing reality in the form of cultural codes. Culture that lives in the community is used as a metaphorical symbol that reflects its experience and knowledge. For connoisseurs of the work can be accepted if there is the same knowledge about the cultural code.